Association between maternal food group intake and birth size - S., L. Loy; M., Marhazlina; J.M., Hamid Jan (Universiti Kebangsaan Malaysia, 2013)
Maternal nutrition is one of the dominant factors in determining fetal growth and subsequent developmental health for both mother and child. This study aimed to explore the association between maternal consumption of food groups and birth size among singleton, termed newborns. One hundred and eight healthy pregnant women in their third trimester, aged 19 to 40 years who visited the Obstetrics and Gynecology Clinic of Hospital Universiti Sains Malaysia completed an interviewed-administered, validated semi-quantitative food frequency questionnaire. The maternal socio-demographic, medical and obstetric histories and anthropometry measurements were recorded accordingly. The pregnancy outcomes, birth weight, birth length and head circumference were obtained from the medical records. The data were analyzed using multiple linear regression by controlling for possible confounders. Among all food groups, fruits intake was associated with higher birth weight (p=0.018). None of the food intake showed evident association with respect to birth length while only fruits intake was associated positively with head circumference (p=0.019). In contrast, confectioneries and condiments were associated with lower birth weight (p=0.013 and p=0.001, respectively). Also, condiments appeared to associate inversely with ponderal index (p=0.015). These findings suggest the potential beneficial effects of micronutrient rich food but detrimental effects of high sugar and sodium food on fetal growth. Such an effect may have long term health consequences to the lives of children.